Production of citric acid from food waste using Aspergillus Tubingensis and Aspergillus Niger - Aabida Parveen; Tooba Naveed; Suraiya Jabeen; Farman Ahmed; Nida Saleem (Advances in Environmental Technology)
Millions of tons of organic waste are produced annually, but no proper disposal method is practiced that minimizes organic waste in an environmentally friendly manner. Such waste has harmful effects on human health and the environment. Organic wastes can be utilized to synthesize industrial products like citric acid. A number of microorganisms have been used in fermentation studies of citric acid. The genus Aspergillus is reported as being a prominent species in the production of a variety of enzymes and organic acids. Exploring more productive strains and valorization of biomass are the most crucial steps in promoting economically viable and useful industrial products such as citric acid, etc. Thus, the present work aimed to assess the potential of locally isolated A. tubingensis for the first time and A.niger for citric acid production. Segregated kitchen waste, crude molasses, and sucrose were used as substrates. Additionally, the effects of pH, carbon, nitrogen, and methanol were also monitored. The findings indicated that the highest yield, i.e., 16.14+0.03g/l, was produced by the A. tubingensisin fermentation media containing sucrose, 1.0% ammonium nitrate (AN), and 2.0% methanol, while 15.97+0.01g/l was produced by the A.nigerin fermentation media containing sucrose, 1.0% ammonium nitrate (AN), and 1.0 % methanol. The addition of methanol in the Aspergillus tubingens is fermentation media produced higher yields of citric acid. The findings demonstrated that A. tubingensis is a potential contender for the production of citric acid. Furthermore, kitchen waste could be a sustainable and cost-effective substrate for citric acid production and can be managed in an eco-friendly way.